Children with lower respiratory tract infections and serum 25‐hydroxyvitamin D3 levels: A case–control study. Issue 10 (1st May 2016) - Velarde López, Angel Alfonso; Gerber, Jeffrey S.; Leonard, Mary B.; Xie, Dawei; Schinnar, Rita; Strom, Brian L.
Summary: Background: Pneumonia is the leading cause of death in children under age of 5 years worldwide. The role of vitamin D in respiratory infections including pneumonia is unclear; therefore, we aimed to determine if children with lower respiratory tract infections had low serum 25‐hydroxyvitamin D3 . Methods: We performed a case–control study of children ages 3–60 months from the Guatemala City metropolitan area, hospitalized with community‐acquired pneumonia between September and December 2012. Controls were selected from the well‐baby/care immunization clinics serving the population from which cases emerged. We analyzed serum 25‐hydroxyvitamin D3 levels and conducted parental interviews to assess subject age, sex, race, feeding type, vitamin D supplementation, frequency of sun exposure, and maternal education. Height and weight were ascertained from medical records. Complete information was available for 70 (83%) of 84 eligible cases and 68 (60%) of 113 eligible controls. Results: The median (IQR) serum 25‐hydroxyvitamin D3 concentration for cases was 23.2 ng/ml (14.4–29.9) compared to 27.5 ng/ml (21.4–32.3) in controls ( P  = 0.006). Multiple regression analysis using an a priori cut‐point for vitamin D of <20 ng/ml showed that children with lower respiratory tract infections were more likely to have low 25‐hydroxyvitamin D3 levels than controls (adjusted odds ratio 2.4, 95% confidence interval 1.1–5.2, P  = 0.02). Conclusions: Children with lower respiratory tract infections in Guatemala had low 25‐hydroxyvitamin D3 levels.Pediatr Pulmonol. 2016;51:1080–1087. © 2016 Wiley Periodicals, Inc.